Production of Cydia pomonella granulovirus (CpGV) in a heteralogous host, Thaumatotibia Leucotreta (Meyrick) (False codling moth) - Chambers, Craig Brian (Rhodes University, Faculty of Science, Department of Zoology and Entomology, 2015)
Cydia pomonella (Linnaeus) (Family: Tortricidae), the codling moth, is considered one of the most significant pests of apples and pears worldwide, causing up to 80% crop loss in orchards if no control measures are applied. Cydia pomonella is oligophagous feeding on a number of alternate hosts including quince, walnuts, apricots, peaches, plums and nectarines. Historically the control of this pest has been achieved with the use of various chemical control strategies which have maintained pest levels below the economic threshold at a relatively low cost to the grower. However, there are serious concerns surrounding the use of chemical insecticides including the development of resistance in insect populations, the banning of various insecticides, regulations for lowering of the maximum residue level and employee and consumer safety. For this reason, alternate measures of control are slowly being adopted by growers such as mating disruption, cultural methods and the use of baculovirus biopesticides as part of integrated pest management programmes. The reluctance of growers to accept baculovirus or other biological control products in the past has been due to questionable product quality and inconsistencies in their field performance. Moreover, the development and application of biological control products is more costly than the use of chemical alternatives. Baculoviruses are arthropod specific viruses that are highly virulent to a number of lepidopteran species. Due to the virulence and host specificity of baculoviruses, Cydia pomonella granulovirus has been extensively and successfully used as part of integrated pest management systems for the control of C. pomonella in Europe and around the world, including South Africa. Commercial formulations have been typically based on the Mexican strain of CpGV. However due to long-term multiple applications of CpGV and the reliance on CpGV in organic farming practices in Europe, resistance to the CpGV-M strain has developed in a number of field populations of C. pomonella. This study aimed to identify and characterize novel isolates of CpGV in South Africa and compare their virulence with the commercial standard CpGV-M. Secondly, since C. pomonella is difficult to culture on a large scale, an alternate method of CpGV production was investigated in order to determine if CpGV could be produced more efficiently and at a reduced cost without negatively impacting the quality of the product. Several isolates of CpGV were recovered either from field collected larvae or from a laboratory-reared C. pomonella colony. Characterisation of DNA profiles using a variety of restriction enzymes revealed that only a single isolate, CpGV-SA, was genetically different from the Mexican strain of the virus used in the commercially available CpGV based products in South Africa. In dose-response bioassays using CpGV-SA, LCâ‚…â‚€ and LCâ‚‰â‚€ values for neonate C. pomonella larvae were 3.18 x 10Â³ OBs/ml and 7.33 x 10â ´ respectively. A comparison of these values with those of CpGV-M indicated no significant difference in the virulence of the two isolates under laboratory conditions. This is a first report of a genetically distinct CpGV isolate in South Africa. The biological activity and novelty of CpGV-SA makes this isolate a potentially important tool for CpGV resistance management in South Africa. In order to justify production of CpGV in an alternative host, studies on the comparative biological performance of C. pomonella and T. leucotreta based on oviposition, time to hatch, larval developmental times and rearing efficiency as well as production costs were performed. Thaumatotibia leucotreta was found to be more fecund and to have significantly shorter egg and larval developmental times. In addition, larval production per unit of artificial diet was significantly higher than for C. pomonella. This resulted in T. leucotreta being more cost effective to produce with implications for reduced insectary space, sanitation practices as well as the labour component of production. Virus yield data generated by inoculation both C. pomonella and T. leucotreta with nine concentrations of CpGV resulted in comparable virus yields, justifying the continuation of the research into production of CpGV in T. leucotreta. It was important to determine the LC and LT values required for mass production of CpGV in late instar T. leucotreta larvae. Dose- and time-response bioassays with CpGV-M were conducted on artificial diet to determine these values. Fourth instar LCâ‚…â‚€ and LCâ‚‰â‚€ values were 5.96 x 10Â³ OBs/ml and 1.64 x 10â µ OBs/ml respectively. LT50 and LT90 values were 81.10 hours and 88.58 hours respectively. Fifth instar LCâ‚…â‚€ and LCâ‚‰â‚€ values were 6.88 x 10â ´ OBs/ml and 9.78 x 10â ¶ OBs/ml respectively. LTâ‚…â‚€ and LTâ‚‰â‚€ values were 111.56 hours and 137.57 hours respectively. Virus produced in fourth instar T. leucotreta larvae was bioassayed against C. pomonella neonate larvae and compared to CpGV-M to establish if production in the heterologous host negatively affected the virulence of the isolate. No significant difference in virulence was observed between virus produced in T. leucotreta and that produced in C. pomonella. The data generated in the bioassays was used in CpGV mass production trials to evaluate production. All production methods tested produced acceptable virus yields. To examine the quality of the virus product, genomic DNA was extracted from larval cadavers and subjected to REN analysis with HindIII. The resulting DNA profiles indicated that the virus product was contaminated with the homologous virus, CrleGV. Based on the above results, the use of T. leucotreta as an alternate host for the in vivo production of CpGV on a commercial basis is not at this stage viable and requires further investigation before this production methodology can be reliable used to produce CpGV. However, this study has shown that CpGV can be produced in a homologous host, T. leucotreta and significant strides have been made towards developing a set of quality control standards that are essential for further development of successful production methodology. Finally a novel isolate of CpGV has been identified with comparable virulence to the CpGV-M. This is an important finding as it has broad reaching implications for resistance management of CpGV products in South Africa.
Keywords: Cryptophlebia leucotreta -- South Africa; Codling moth -- South Africa; Apples -- Diseases and pests -- South Africa; Codling moth -- Biological control -- South Africa; Insect pests -- Biological control -- South Africa; Biological pest control agents -- South Africa; Baculoviruses -- South Africa